Pengaruh Pengetahuan Lingkungan Dan Persepsi Green Economy Terhadap Minat Green Entrepreneurship Anggota Umkm Seroja Kabupaten Deli Serdang - Ginting, Erisa Br; Siregar, Dahrul (Universitas Medan Area, 2024)
The purpose of this research is to determine the influence of environmental knowledge and perceptions of the green economy on the interest in green entrepreneurship of members of the Seroja MSMEs, Deli Serdang Regency. The type of research carried out is associative research with a quantitative approach and the research measurement scale is measured using a Likert scale. Data collection methods were carried out by interviews, questionnaires and documentation studies. The population in this study were 60 members of Seroja MSMEs who were also used as samples. Statistical analysis was carried out using multiple regression, with hypothesis testing and classical assumption testing. The results of this study conclude that all hypotheses are accepted, namely the influence of environmental knowledge (X1) on interest in green entrepreneurship (Y), a significant value smaller than 0.05 or a value of 0.000 0.05, the influence of green economy (X2) on green entrepreneurship (Y ) significant value is smaller than 0.05 or 0.003 0.05 and Environmental Knowledge and Green Economy simultaneously have a positive and significant effect on interest in green entrepreneurship.